Perbedaan Media Poster dan Media Audiovisual (Video) Tentang Resusitasi Jantung Paru (RJP) Terhadap Efikasi Diri (Studi Siswa-siswi SMKN 1 Banjarbaru) - Ilham Bimantoro; Abdurahman Wahid; Herry Setiawan (Nerspedia, 2022)
Background: Cardiovascular disease in the form of cardiac arrest that occurs outside the hospital causing the death of more than 17 million people. However, cardiac arrest can be treated with Basic Life Support (BLS) in the form of Cardio Pulmonary Resuscitation (CPR) using health education media with audiovisual media (video), where audiovisual media (video) is better at conveying information. At SMK 1 Banjarbaru there has not yet there about BHD health education especialy CPR. BLS Health Education about RJP using audiovisual media (video) can increase knowledge and improve the self-efficacy of students in helping victims of cardiac arrest outside the hospital.Objective: To find out the differences between poster media and audiovisual media (video) about cardio pulmonary heart resuscitation (CPR) on self-efficacy in students of SMKN 1 Banjarabaru.Method: This study uses a quasy experimental design method with a post-test only design, data collection techniques that use probability sampling with a simple random sampling approach. The number of samples is 84 respondents and is divided into 2 groups, that is the poster group poster media and audiovisual (video) media. Data were collected using a self-efficacy questionnaire sheet. Analysis of the data used is the Mann Whitney test.Results: From the statistical results using the mann-whitney test obtained p-value of 0,000. With the value obtained (p-value 0,000 <α = 0.05) on students' self-efficacy, which means that there is a difference using poster media and video media about RJP on self-efficacy in students of SMK 1 Banjarbaru. The results showed an average value of 28.40 in audiovisual media (video) was higher than in poster media with an average value of 23.83.